Developing a “Fast-Track” Strategy for Interventional Management of Patients With Idiopathic Intracranial Hypertension - Miri, Shahnaz; Moghekar, Abhay; Carey, Andrew R.; Gailloud, Phillipe; Miller, Neil R. (Frontiers in Ophthalmology, 2022)
Idiopathic intracranial hypertension (IIH) has an increasing incidence worldwide over the past decade, with a high economic burden on patients and society. Up to 10% of patients with IIH have progressive visual decline requiring an invasive intervention (including cerebrospinal fluid shunting, cerebral dural sinus stenting, or optic nerve sheath fenestration [ONSF]). IIH patients with visual decline usually undergo evaluation and initial management through the emergency department (ED) and commonly have a long hospital stay due to the lack of a dedicated methodology for the evaluation and management, particularly in patients who present with visual loss (ie, fulminant IIH). This paper aims to discuss the need for the development and implementation of a multidisciplinary "fast-track" strategy for the evaluation and management of patients with fulminant IIH or those with a suboptimal response to the maximum tolerated medical treatment at risk for visual loss. We suggest that such a program could reduce hospital stays and ED visits and therefore reduce healthcare costs and improve patient outcomes by accelerating the management process.